An Evaluation of the Professional Development Component of the Overseas Doctors Training Programme - Hawken, Susan James (Auckland University of Technology, 2003)
This study set out to determine how useful the professional development component of the Overseas Doctors Training Programme in Auckland was in preparing these doctors to work in the New Zealand health context. An anonymous postal questionnaire was sent to all 89 doctors that passed the first three cohorts of the Overseas Doctors Training Programme, resulting in a response rate of 30%. The main findings were that the professional development component was seen as valuable and effective with respect to improving communication skills, and patient-centred consultations. There was a significant increase in the level of comfort with communicating with patients after the course and once they were in a clinical setting (p<0.001) and with communicating effectively and safely with Maori (p<0.001). The ethical, legal and reflective practice sessions also prepared these doctors adequately to work in New Zealand. Limitations of the study included the low response rate, the potential for response bias in the self-rating scale used, and that these doctors’ perceptions of skill, not actual clinical performance, were measured. This evaluation discusses the multiple contextual and in particular cultural factors that influence the learning on the programme and the barriers to success for these overseas trained doctors, including English proficiency, previous experience, and stress. Recommendations include more emphasis to be given to English proficiency prior to the course and the development of tools to help screen for those doctors who are most likely to be able to make the changes in behaviour required to practise in New Zealand.
Keywords: Physicians; Foreign; Professional education